Beyond the classical "living high" paradigm in winter sports: Lessons from summer sports - Brocherie, F.; Forot, J.; Millet, G. P. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Winter sports events are generally performed at low to moderate altitudes, requesting prior acclimatization/acclimation (the classical "living high" paradigm) to counteract the negative effect of lower oxygen availability (physiology) and reduced air resistance (skill components). However, the evolving boundaries of altitude/hypoxic training [1] as well as the potential of other environmental stress-based interventions (e.g. hyperoxia for recovery or heat for cross-adaptation) tested in summer sports contribute to an increase body of knowledge and evidence that could be translated to winter sports.